Manufacturing Engine Test Bed Dle-55cc Single Cylinder Petrol - Infitah Hilmiah, Siti Iin; Mulyani, Sri; Rahendra P, Lazuardy (Vortex, 2021)
The engine test bed is a tool used for testing in the development of new aircraft when it is installed into the aircraft to determine the capabilities of each engine. This engine test bed research aims to meet the needs of the learning process in supporting the practicum. By determining the geometry, modeling, material selection, manufacture, and testing of the engine test bed it will be known that the engine performance is good before use. The method used is a practical and analytical method to analyze the data that has been obtained from the test. The object of research used in this study is a dle-55cc engine. based on the results of testing the results of the thrust that compares with the static value of the thrust calculator, the average difference is obtained. From the results of the comparison of errors on the test equipment, the 22×8 propeller (4.5cm chord) obtained an average error of 4.178%. While the propeller 22×8 (chord 5cm) the error generated is 3.719% and from the value of fuel consumption obtained it produces 588,600-20,708 (N/kW.hr) this shows a good level of decline, so the engine used is more efficient in its use. From the test results, it can be said that the engine test bed has accuracy and can produce good engine performance to be used as a testing and other learning tool.